Exponential decay for a Klein–Gordon–Schrödinger system with locally distributed damping - Poulou, Marilena; Filippakis, Michael; Zanchetta, Janaina [UNESP] (University of Szeged, 2024)
A coupled damped Klein–Gordon–Schrödinger equations are considered where Ω is a bounded domain of R2, with smooth boundary Γ and ω is a neigh-bourhood of ∂Ω satisfying the geometric control condition. The aim of the paper is to prove the existence, uniqueness and uniform decay for the solutions.
Keywords: asymptotic behavior; existence and uniqueness; exponential stability; Klein–Gordon–Schrödinger; localized damping